Analisa Perbandingan Laju Korosi Lambung Kapal Dengan Aplikasi Paduan Alumunium - (Program Diploma III Teknik Perkapalan Fakultas Teknik Universitas Diponegoro Semarang), Eko Juliant; (Program Diploma III Teknik Mesin Fakultas Teknik Universitas Diponegoro Semarang), Seno Darmanto; (Program Dipoma III Teknik Kimia Fakultas Teknik Universitas Diponegoro Semarang), Edy Supriyo (Teknis, 2014)
The research aims determine the effectiveness of the use of aluminum alloy as sacrificial anode for cathodic protection of hull plates and knows the needs of sacrificial anode that is used to slow the average rate of corrosion in the hull plates in seawater. This research method laboratory experiments. Test speciment for experimental laboratory is a steel plate AISI E 2512, three kinds of aluminum alloy sacrificial anode products are different (the product A, Al = 86.118%, the product B Al = 85.097% and the product C Al = 97.665%) and use of sea water mediaÂ with a salinity of 37 %.Â Results of corrosion testing in the laboratory can prove that among of the three aluminum alloy sacrificial anode mounted on steel plates of AISI E 2512 ships haven is the most optimal performance is the product of aluminum alloy sacrificial anode C, because it has the average corrosion rate of the lowest vessel steel plate at 0.065 mm/year. From this research it is known that aluminum alloy sacrificial anode product C has the optimal performance, meaning it slows the rate of corrosion of steel plate AISI E 2512 that can truly serve as the sacrificial anode.Â Key words: Ship steel plate , Aluminum alloy sacrificial anode, Corrosion rate